PENGARUH KUALITAS PRODUK, HARGA PRODUK, BRAND IMAGE, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN MESIN PARUT DI CV SENENG BARENG SEJAHTERA - Annisa Marinda Salam (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2019)
This study aims to test Product quality, product price, Brand Image, And Promotion Against Consumer Buying Decision of Grate Screw CV Seneng Bareng Sejahtera. The object of research is consumer CV Seneng Bareng Sejahtera. Respondents were 100 people selected based on incidental sampling method. Hypothesis testing is done by using multiple linear regression analysis with SPSS 21 program. The result of research indicate that product quality and price variant have significant effect to purchasing decision. Brand image and promotion have no significant effect on purchasing decision.